Biological Evidence Management at the Crime Scene: An Overview (Indian Journal of Forensic Medicine & Toxicology, 2023)
Crime scene serves as the starting point for forensic science and can generate valuable data that must bemeticulously, methodically, scientifically, and lawfully gathered. If the crime scene is not handled appropriately,it can become misleading and render crucial information useless, leading to an investigation on the wrong path.Forensic science has undergone a revolution thanks to the use of DNA technologies. Many times, due to theinvestigator’s lack of scientific expertise regarding the proper collection, preservation, storage, and transportationof biological evidence, the investigator is unable to acquire accurate DNA analysis results, which reduces the valueof the evidence in court. Purity, quantity, and rate of DNA degradation are just a few of the many variables thatgo into creating a decent DNA profile from a biological sample. We highlight and provide useful strategies andrecommendations to assist medical, forensic, and law enforcement professionals in handling biological evidencesfor DNA analysis to prevent contamination, deterioration, and loss of biological evidence’s value.
Keywords: Crime Scene, Biological evidence, Contamination, Forensic Science